Getting a jump on malaria [health care]. - Aaronson, L. (IEEE spectrum)
This paper discusses how data obtained from Earth-sensing satellite systems can be used in the efforts to prevent and treat malaria in developing countries especially in Africa. The paper describes how representatives from WHO and various space and oceanographic agencies have agreed to meet under the auspices of the Global Earth Observation System of Systems (GEOSS) to advance human health by better integrating data from a wide variety of Earth-sensing systems including ocean buoys, seismic sensors, and satellites. One element of this plan, with important implications for epidemic forecasting and disease treatment, involves introducing diverse data producers like the European Space Agency and the NOAA to prospective data users such as the WHO and other health policymakers.